Energy and macronutrient intakes and food sources in preschool children: Thai NHES IV - Warapone Satheannoppakao (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: Examine intakes of energy and macronutrients, and identify their food sources, in Thai preschool children. Material and Method: Data from the Thai National Health Examination Survey (NHES) IV were used. Mothers/caregivers were interviewed regarding their children’s 24-hour-dietary intake. Dietary data were analyzed for energy and macronutrients, and their food sources were investigated. Due to skewed data, Mann-Whitney U test was used to compare energy and macronutrient intake between sexes and age groups. Results: Among 256 preschool children, more than 90% had protein intakes higher than the recommended level. Only 12.7 to 29.0% met the recommended intake for energy. Amounts of carbohydrate and fat consumed varied from below to above the Dietary Reference Intake (DRI) recommendation. Intakes of carbohydrate in boys and fat in girls were statistically different between age groups (p < 0.05). Fifty to 60% of energy came from dairy products, grains and starchy products. The major carbohydrate contributors were grains and starchy products. Dairy products were the main source of protein. Important food sources of fat were dairy products for one- to three-year-old children and fat and oils for four- to five-year-old children. Conclusion: Thai preschool children have inappropriate intakes of energy and macronutrients. Dairy products and grains and/or starchy products were the main sources of energy, carbohydrate, and protein. Dietary fat sources varied by age group.